(3OQGSGJ fXQjI hJWHjbjIs - (3SYjO YHO GdYRjR(B, (3YKeGfs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3GdCSS GdEbJUGOjI ddfTGW GdMchej , GdSjGSI GdJSYjQjI aj bWGY GdNOeGJ GdYGeI , GdNUNUI hGdcaGAI GdEbJUGOjI, HQGeL GdJNUjU hCShGb QCS GdeGd aj GdOhd GdfGejI, GfJGLjI GdfabI GdYGeI aj bWGY GdNOeGJ GdUMjIs
Keywords: (3GdbWGY GdYGes; (3GdeQGab GdYGeIs; (3GdeTQhYGJs